Pain Pressure Threshold as a Non-Linear Marker of Neural Adaptation in Amputees: Evidence from the DEFINE Cohort - Marta Imamura; Anna Carolyna Gianlorenço; Guilherme J. M. Lacerda; Linamara Rizzo Battistella; Felipe Fregni (NeuroSci)
Background: Amputation poses significant physical, psychological, and emotional challenges, with chronic pain being one of the most debilitating outcomes. Pain Pressure Threshold (PPT), a measure of nociceptive sensitivity, is a valuable tool for assessing changes in pain perception. Understanding PPT modulation in amputees is crucial for uncovering the mechanisms underlying pain and developing targeted interventions for pain management. Objective: This study aimed to evaluate PPT in amputees and identify factors associated with PPT variation in this population. Methods: This cross-sectional study analyzed neurophysiological, clinical, and demographic data from 86 amputee patients. PPT was assessed as the primary outcome, and its associations with demographic and clinical predictors were examined using both linear and quadratic regression models. Results: Multivariate analysis identified a significant association between PPT and biological sex, with females exhibiting lower PPT values than males. Quadratic regression analyses revealed inverted U-shaped associations between PPT and age, BMI, and duration since amputation. PPT increased with age, peaking at 45.8 years, followed by a decline. Similar patterns were observed for BMI, peaking at 27.0 kg/m2, and for amputation duration, peaking at 26.6 months. Conclusions: Our findings indicate that sex, age, BMI, and time since amputation are significant factors influencing PPT in amputees, with nonlinear relationships observed for age, BMI, and amputation duration. These results suggest that physiological and disease-related factors (such as age, BMI, and duration of injury) have specific peaks for optimal PPT, highlighting their role in the brain’s compensatory system and potential implications for targeted pain management strategies.